Array - J ayanti, Oktavia Tri; Samsul, Suwarno Imam (LATERNE, 2021)
Listening skills are one of the four skills that must be mastered in learning German. In order to achieve a learning goal, the teachermust be able to manage the existing learning environment. The learning media in question is an Android-based learning media in theform of a "Dimosa" digital application, to improve listening skills in German. Of the many methods of learning found a method ofusing "Dimosa" media that simplifies and speeds up learning. Android-based learning media in the form of a "Dimosa" digitalapplication was chosen because the use of this media is very easy and practical so that it can be used anytime and anywhere. Theformulation of the problem in this research is how Android-based learning media in the form of Dimosa digital applications forlistening skills can assist in the learning process of teaching German in Buduran 2 Vocational High School grade X semester 1. Thepurpose of this study is to manufacture and develop learning media in the form of digital applications "Dimosa" is an Android-basedapplication that is feasible to be applied as a learning media for listening skills in German Language Vocational High School2 Buduran class X semester 1. This type of research is R&D (Research andDevelopment) which is described qualitatively.Dimosa media obtained from the questionnaire results of material experts and media experts. The results of this study indicate thatDimosa media can be applied in learning German listening skills for students in class X Semester 1 of SMK 2 Buduran.Learning techniques using Dimosa media have an influence on listening skills in Class X Semester 1 student of Buduran 2Vocational High School, this can be proven from the evaluation results obtained from the results of material and media expertvalidation. Based on the results of the data analysis technique, it is known that the results of the presentation or the value of themedia feasibility have been fulfilled both normally and visually by <80%, which means it is very feasible. Thus it can beconcluded that Dimosa media has a significant influence on listening skills in class X Semester 1 student of SMK 2 Buduran. This canbe proven from the results of the questionnaire evaluating material experts and media experts as well as Dimosa's own media. Keywords: content, formatting, article